The Influence of Orbital Forcing on 10Be Deposition in Greenland Over the Glacial Period - Sturevik-Storm, Anna; Zheng, Minjie; Aldahan, Ala; Possnert, Göran; Muscheler, Raimund (Frontiers in Earth Science, 2021)
Understanding the transport and deposition of the cosmogenic isotope 10Be is vital for the application of the isotope data to infer past changes of solar activity, to reconstruct past Earth's magnetic field intensity and climate change. Here, we use data of the cosmogenic isotope 10Be from the Greenland ice cores, namely the NEEM and GRIP ice cores, to identify factors controlling its distribution. After removing the effects of the geomagnetic field on the cosmogenic radionuclide production rate, the results expose imprints of the 20-22 ka precession cycle on the Greenland 10Be records of the last glacial period. This finding can further improve the understanding of 10Be variability in ice sheets and has the prospect of providing better reconstructions of geomagnetic and solar activity based on cosmogenic radionuclide records.